KONSEP DIRI DAN PRESTASI BELAJAR - Subaryana Subaryana (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2015)
The self-concept is an individual view of themselve , the more positive their self-concept, the more positive the individual sees themselve and also the view of themselve and their environment. Students who have a positive self-concept tend to view learning as a necessity or study because of the motivation comes from themselves, so their study results tend to be the maximum. While students who have a negative self-concept study tend to view it as an obligation to do or because others assured that learning is beneficial, so they study because of the element of compulsion to obtain value or graduation , therefore their study results tend to be less than the maximum or lower. Thus the self-concept has a very significant correlation to learning achievement. Based on the situation it has become an obligation for teachers and parents to help students to develope their positive self-concept